Pendampingan Guru Madrasah Banua Sendana untuk Meningkatkan Kompetensi Pedagogik melalui Implementasi Brain Based Learning - Usri Usri; Zulianah Sunusi; Aan Setiawan; Nurul Hazirah (Universitas Muhammadiyah Semarang, 2024)
This study aims to improve the pedagogical skills of MA DDI Banua Sendana teachers through the implementation of brain-based learning. The method used in the research is Community-Based Research. Data on the improvement of pedagogical competence ability was analysed using inferential statistics, while data on the implementation of brain based learning was analysed using descriptive statistics. The mentoring activities carried out to improve teachers' pedagogical competence consist of: 1) the brain-based learning training stage begins with a pretest of pedagogical competence related to brain-based learning; 2) the stage of developing learning tools with the ADDIE approach starting at the analysis, design, development, implementation, and evaluation stages of the developed tools; and 3) the evaluation stage of the implementation of assistance consisting of an evaluation of the improvement of teacher pedagogical competence and a survey of teacher satisfaction with the implementation of assistance. The teacher response to the implementation of the service shows that there are 75% or 9 teachers who are in the very satisfied category and 25% or 3 teachers who are in the satisfied category. So that there are no teachers who are in the moderately satisfied category and the dissatisfied category.